Development of a full micro-scale spatially offset Raman spectroscopy prototype as a portable analytical tool. Issue 2 (14th December 2016) - Realini, Marco; Conti, Claudia; Botteon, Alessandra; Colombo, Chiara; Matousek, Pavel
Abstract : We present, for the first time, a portable full micro-Spatially Offset Raman Spectroscopy (micro-SORS) prototype permitting the in situ analysis of thin, highly turbid stratified layers at depths not accessible to conventional Raman microscopy. Abstract : We present, for the first time, a portable full micro-Spatially Offset Raman Spectroscopy (micro-SORS) prototype permitting the in situ analysis of thin, highly turbid stratified layers at depths not accessible to conventional Raman microscopy. The technique is suitable for the characterisation of painted layers in panels, canvases and mural paintings, painted statues and decorated objects in cultural heritage or stratified polymers, and biological, catalytic and forensics samples where invasive analysis is undesirable or impossible to perform. The new device is characterised conceptually in polymer and paint layer systems. The provision of portability with full micro-SORS delivers subsurface micro-SORS capability unlocking the non-invasive and non-destructive potential of micro-SORS at its most effective form permitting it to be applied to large and non-portable objects in situ without recourse to removing micro-fragments for laboratory analysis on benchtop Raman microscopes.